Does Money Still Matter? Attainment and Earnings Effects of Post-1990 School Finance Reforms - Rothstein, Jesse; Schanzenbach, Diane Whitmore (Journal of Labor Economics, 2022)
In two 1992 papers, Card and Krueger used labor market outcomes to study the productivity of school spending. Following their lead, we examine the effects of post-1990 school finance reforms on students’ educational attainment and labor market outcomes. Using a state-by-cohort panel design, we find that reforms increased high school completion and college-going, concentrated among Black students and women, and raised annual earnings. The reforms also increased the return to education, particularly for Black students and men, driven by the return to high school.